Precooling with crushed ice: As effective as heat acclimation at improving cycling time-trial performance in the heat - Zimmermann, M.; Landers, G.; Wallman, K.; Kent, G. (International Journal of Sports Physiology and Performance, 2018)
This study compared the effects of precooling (ice ingestion) and heat-acclimation training on cycling time-trial (CTT) performance in the heat. Fifteen male cyclists/triathletes completed two 800-kJ CTTs in the heat, with a 12-d training program in between. Initially, all participants consumed 7 g/kg of water (22°C) in 30 min before completing an 800-kJ CTT in hot, humid conditions (pre-CTT) (35°C, 50% relative humidity [RH]). Participants were then split into 2 groups, with the precooling group (n=7) training in thermoneutral conditions and then undergoing precooling with ice ingestion (7 g/kg, 1°C) prior to the final CTT (post-CTT) and the heat-acclimation group (n=8) training in hot conditions (35°C, 50% RH) and consuming water (7 g/kg) prior to post-CTT. After training in both conditions, improvement in CTT time was deemed a likely positive benefit (precooling -166± 133 s, heat acclimation -105±62 s), with this result being similar between conditions (d=0.22, -0.68-1.08 90% confidence interval [CI]). Core temperature for post-CTT was lower in precooling than in heat acclimation from 20 min into the precooling period until the 100-kJ mark of the CTT (d>0.98). Sweat onset occurred later in precooling (250±100 s) than in heat acclimation (180±80 s) for post-CTT (d=0.65, -0.30-1.50 90% CI). Thermal sensation was lower at the end of the precooling period prior to post-CTT for the precooling trial than with heat acclimation (d=1.24, 0.90-1.58 90% CI). Precooling with ice ingestion offers an alternative method of improving endurance-cycling performance in hot conditions if heat acclimation cannot be attained.